VALUE ADDED CREATION FOR PRIVATE-PUBLIC PARTNERSHIP PROJECTS - A. Kuznetsov (Вестник университета, 2016)
The article is devoted to the problem of value added analysis applied for the projects of private-public partnership. The final value and added value of the object of infrastructure created within private-public partnership project is viewed by vertical integrated chain of companies as well as by factors of production.